WACANA TUTUR DALAM KIDUNG COWAK: ANALISIS STRUKTUR DAN MAKNA - Arsani, Ni Nyoman (Humanis, 2016)
Kidung Cowak contains values ??that high philosophy and also full of meaning, as well as the mandate. There are a lot of advice given in the form of criticism of the things that have been commonplace in society, but not in accordance with the teachings of Agama. Teori literature used in this research is the theory of structural and semiotic theory. The analysis in this paper examines the structure of the unit forms that include diction, imagery, style, Ritma and rhymes; unit contents include themes, taste, tone, and mandate. While the author examines the semiotic analysis of the element symbols, because the element symbol is more dominant than the index elements and icons. Symbol element is then searched its meaning. Methods and techniques used include three stages, namely stages providing data, data analysis stage, and the stage presentation of the results of the data analysis. Results of this research is to know the structure of Kidung Cowak, and can know the meaning contained in it, meaning that obtained in the "Discourse Said in kidung Cowak Text: Analysis of Structure and Meaning" on kasuñatan (emptiness), mind, karma phala, heaven, moksha and jagadhita, rwa bhineda and other meanings are grouped into text form, which includes the form of ideas, a form of behavior and form of artifacts.
Keywords: kidung, cowak, meaning